SUB-GENRES MILITARY LITERATURE IN CHINESE LITERATURE - Hin Goan Gunawan; AINANI TAJRIYANI HS (Bambuti, 2021)
Chinese literature has various genres, one of which is Military Literature. The short story entitled Sabuk Tentara Rusia by Ma Xiaoli is a text that tells about the relationship between the Russian Army and the Chinese Army and shows the cultural differences between the two countries. The analysis with the modern semiotic approach used in this study succeeded in mapping the elements of the Military Literature sub-genre in Ma Xiaoli's Sabuk Tentara Rusia in detail and comprehensively, and was able to confirm that the text is part of the Military Literature sub-genre in Chinese literature.